Face Song Player According to Facial Expressions - Samule Lee; Seong-Yoon Shin (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Contemporary people have highly insufficient time and means of relieving their stress. Provision of a program that can solve such stress in daily life would make one’s life substantially more enjoyable. In this thesis, Face Song Player, which is a system that recognizes the facial expression of an individual and plays music that is appropriate for such person, is presented. It studies information on the facial contour lines and extracts an average, and acquires the facial shape information. MUCT DB was used as the DB for learning. For the recognition of facial expression, an algorithm was designed by using the differences in the characteristics of each of the expressions on the basis of expressionless images. Facial expression is extracted by acquiring information on the eyes, eyebrows, eyelids, mouth, lips and nasal cheeks for expressions of happiness, surprise and sorrow as well as absence of expression. There is an advantage of being able to obtain a substantial effect with very low cost through this system.